Visual preferences for educational game designs through the graphic style approaches - Lee, Lilian Shiau Gee; Jasni Dolah; Victor B. Pangayan (Penerbit UMS, 2019)
The role of visual design in educational games is not only for beauty, but also for critical motivation to engage students in nurturing emotional values and thus enhancing their positive experiences. In terms of visual design, graphic style is key to re-evaluating the power and suitability of visual design in variety and rapidly changing game. This paper discusses the importance of graphic styles and their impact on educational games in the context of improving students' learning through play. The influence of design based graphic styles, the graphic characterization and the relationship of graphic trend in design innovation should be emphasized to determine how design can influence the game visualization.